NEW EVIDENCE FROM THE EFFICIENT MARKET HYPOTHESIS FOR THE NIGERIAN STOCK INDEX USING THE WAVELET UNIT ROOT TEST APPROACH - Kelikume, Ikechukwu (The Journal of developing areas, 2016)
The efficient market hypothesis (EMH) assumes the absence of asymmetric information in trading activities in a typical stock market. The EMH has been tested extensively in the developed market economy with mixed results, but very little contribution has been made on the subject matter in developing market economy because of the presence of asymmetric information, institutional constraints and poor data collection method. Validating the hypotheses for the African economy has remained of great interest to researchers and investors given the repeated emphasis on the African economy as the next frontier of economic growth. Issues surrounding the EMH in developing economy rest on the possibility of exploiting the stock market to make quick returns. The validity of this statement remains to be tested empirically for the developing market economy. This paper investigates the EMH for a major developing African economy-Nigeria being the most populous country in Africa and the second financial hob in Africa, next only to South Africa. The study seeks to test the efficiency of the Nigerian stock market, using a wavelet unit root test with different lags and other traditional random walk testing procedure. The use of the wavelet unit root test entails the decomposition of the variance of the time series stochastic process into the variance in its high and low-frequency series. The study made use of monthly average stock price index of the Nigeria Stock Market over the sample period 1985 to 2015 to carry out the test. The result obtained from the wavelet-based unit root tests showed clear and conclusive evidence that the Nigerian Stock Market follows the random walk behavior during the period of the study and that the Nigerian Stock Market is efficient. In other words, stock prices fully reflect all the available information existing in the market and investors, armed with the trading rules, cannot exploit the market to earn extraordinary returns. This has vital implications for speculators, investors and rent-seekers hoping to capitalize on the unstructured nature of a typical developing market economy to make quick wins. Since the Nigerian Stock Market is efficient, investors should desist from futile attempts to forecast long-run share prices with the hope of making a quick, sustained win in the market.